Diversity of true mangroves and their associates in the Kundapura region, Udupi district, Karnataka, Southwest coast of India - M, Vijaya Kumar K; Kumara, Vijaya (Current Botany, 2012)
The present study documents the diversity of true mangroves and their associates, in four selected sites of Kundapura, Udupi district, Karnataka, Southwest coast of India, for a period of two years from April-2010 to March-2012. These places are far from one another and the mangrove species diversity varies from one place to another, due to factors such as climate, tidal factors and anthropogenic pressures. Nine true mangrove floral species belonging to six families and ten associated floral species belonging to nine families were identified along the inundated and the adjacent regions at the study sites. This write up discusses the need of present study is to gain knowledge about the mangrove flora in order help conservation of mangrove ecosystem.